Digital Business Communication Strategies for Increasing MSMEs Brand Awareness - Winda Sari; Havis Aravik; Ahmad Tohir; Dwi Noviani; Dodi Irawan (Penerbit dan Percetakan CV. Picmotiv, 2025)
Business communication strategy plays an important role in increasing brand awareness of MSMEs and expanding business reach, the main objective of this researcher is to analyze business communication strategies and increase brand awareness of MSMEs in the digital era, this study uses a descriptive method with a quantitative approach, in order to provide an overview of the use of technology by MSMEs, The results of the study show that social media such as Instagram, Facebook, and WhatsApp are the main platforms for digital marketing because of the ease of accessing the internet, Strategies such as promotion, communication, bring benefits to increasing brand visibility and sales, challenges for MSMEs such as limited digital literacy, internet connectivity, market competition. therefore, increasing the capacity for technological adaptation is the main key to building brand awareness effectively. So the importance of creative data-based digital communication strategies supports the development of MSMEs in the digital era.